Respuesta :
For this case we have by definition, that the equation of a line in the point-slope form is given by:
[tex](y-y_ {0}) = m (x-x_ {0})[/tex]
Where:
m: It's the slope
[tex](x_ {0}, y_ {0}):[/tex] It is a point through which the line passes.
[tex]m = \frac {y2-y1} {x2-x1}[/tex]
We have as data two points, replacing:
[tex]m = \frac {1-6} {0 - (- 5)}\\m = \frac {1-6} {0 + 5}\\m = \frac {-5} {5}\\m = -1[/tex]
We substitute a point, then the equation is:
[tex](y-1) = - 1 (x-0)\\(y-1) = - x[/tex]
Answer:
[tex](y-1) = - x[/tex]
Answer: [tex]y-6=-(x+5)[/tex]
Step-by-step explanation:
The Point-slope form of the equation of the line is:
[tex]y-y_1=m(x-x_1)[/tex]
Where "m" is the slope of the line and [tex](x_1,y_1)[/tex] is a point on the line.
We know that this line passing through the points (-5,6) and (0,1), then we can find the slope with this formula:
[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]
Substituting, we get:
[tex]m=\frac{1-6}{0-(-5)}=-1[/tex]
Finally, we can substitute the point (-5,6) and the slope into [tex]y-y_1=m(x-x_1)[/tex], then:
[tex]y-6=-(x-(-5))[/tex]
[tex]y-6=-(x+5)[/tex]